Storytelling as a tool for scientific dissemination: Reflections on scientific information or misinformation on Internet social networks - Alvarado Chávez, Troi Ernesto (Scripta Mundi, 2022)
The internet, digital communication and social media have changed in the way we live, connect and inform ourselves. This change has been more radical after the confinement caused by the Covid-19 pandemic, which accelerated the processes of digitalization of the information. In the midst of this communication context in which information, science and knowledge, as well as pseudoscience, falsehood and disinformation are available to everyone, the academy evolves and reinvents itself. Many scientists seek to reach the masses in order to communicate advances and discoveries through different media. Telling stories or storytelling has become a way to share the benefits of scientific discoveries with humanity. This essay intends to analyze the current state of the art on scientific dissemination, and the propagation of pseudosciences, as well as the communication problems that have not allowed science to be effectively connected with the common citizen as a beneficiary of scientific discoveries. The current state of the use of storytelling as a tool to bring advances in scientific and academic knowledge to the common citizen will be studied. Based on these reflections, it is intended to establish the bases for future researches in which we can know which are the most effective forms of communication to disseminate knowledge and science for the benefit of humanity.